Consumer Search: What Can We Learn from Pre-Purchase Data? - Elisabeth Honka; Stephan Seiler; Raluca Ursu (Center for Economic Studies and ifo Institute (CESifo), 2023)
Researchers are increasingly able to observe consumers' behavior prior to a purchase, such as their navigation through a store or website and the products they consider. Such pre-purchase (or search) data can be valuable to researchers in a variety of ways: as an additional source of information to estimate consumer preferences, to understand how firms can influence the search process through marketing mix variables, and to analyze how limited information about products shapes market outcomes. We provide an overview of these three areas with a particular emphasis on online and offline retailing.
Keywords: D43; D83; L13; 330; consumer search; limited information; consideration sets; retailing